2016
DOI: 10.3920/wmj2015.1917
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence ofFusarium species and mycotoxins in wheat grain collected in the Czech Republic

Abstract: A complex of Fusarium spp. causes Fusarium head blight (FHB) on wheat and also on barley. Infection with FHB results not only in yield loss, but also causes depreciation of the harvested product due to the accumulation of toxins such as deoxynivalenol produced by Fusarium spp. The flowering time is a very susceptible period for primary infection. One reason might be that during this period spores can get into the opened wheat florets where they may later cause infection. Initial symptoms of infection of a whea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…This is in agreement with the findings of Nitzsche et al (2002), which described the risk of FHB in the Saxonia region for wheat following various precrop types, and concluded that corn as a pre-crop increased the risk of Fusarium infestation. A 10-year survey of randomly collected winter wheat samples within the Czech Republic also revealed the significant adverse effect of corn as the pre-crop on the accumulation of DON in wheat grain (Chrpová et al 2015). Moreover, DON production by both of the DONproducing species F. culmorum and G. zeae was significantly higher in mixed infections with other species.…”
Section: Discussionmentioning
confidence: 97%
“…This is in agreement with the findings of Nitzsche et al (2002), which described the risk of FHB in the Saxonia region for wheat following various precrop types, and concluded that corn as a pre-crop increased the risk of Fusarium infestation. A 10-year survey of randomly collected winter wheat samples within the Czech Republic also revealed the significant adverse effect of corn as the pre-crop on the accumulation of DON in wheat grain (Chrpová et al 2015). Moreover, DON production by both of the DONproducing species F. culmorum and G. zeae was significantly higher in mixed infections with other species.…”
Section: Discussionmentioning
confidence: 97%
“…Second to enniatin B, beauvericin showed the highest concentrations in oats with a maximum level of 110 µg kg −1 . The emergence of more Fusarium mycotoxins has been observed in both south and central European countries such as Poland, the Czech Republic, and Italy (Juan et al, ; Bryla et al, ; Chrpová et al., ), but also in the Nordic countries Norway and Finland (Uhlig et al, ). The concentration levels observed for Danish crops in the present study, as well as those we observed in previous studies on whole fresh and ensiled Danish maize (Sørensen et al, ; Storm et al, 2014), are comparable for the Nordic countries.…”
Section: Discussionmentioning
confidence: 99%
“…In last years, data on the occurrence of beauvericin (BEA) and enniatins (ENs) in livestock feedstuff have been reported. BEA and ENs are predominantly found in cereals (grains and products) [44,[54][55][56][57][58][59]. However, they have also been detected in by-products from various types of industry [60,61] so their presence was logically noted also in compound feeds for livestock animals [62][63][64].…”
Section: Presence Of Beauvericin and Enniatins In Feedstuffsmentioning
confidence: 99%
“…Co-occurrence of ENs and BEA with other fusarium mycotoxins such as deoxynivalenol or nivalenol was often reported [55,[86][87][88]; thus, not only the toxicity of individual mycotoxins, but also their possible synergistic, additive, or antagonistic effects on animals, should be taken into consideration. To our knowledge, these effects on various cells were described for combinations of different Fusarium mycotoxins, such as BEA, T-2 toxin (T-2) and DON; ENs A, A1, B, and B1; BEA, DON, enniatin B, FB1, T-2, and ZEA; T-2 toxin and enniatin B1 (recently reviewed by Smith et al [89], Mallebrera et al [90] and Prosperini et al [91]), DON, enniatin B and alternariol [92]; DON, BEA, ZEA, enniatin A, A1, B, B1, alternariol, tentoxin, and mycophenolic acid [93] or BEA and ZEA derivates [94].…”
Section: Presence Of Beauvericin and Enniatins In Feedstuffsmentioning
confidence: 99%